Primer vojskovanja staroselskih populacij: kmetov iz Chiapasa in Yanomamov - Kvaternik, Ines (Teorija in praksa, 1999)
The aggression is the central part of human nature to a such extent that it is almost always the reason for fighting among 'primitive' peoples. It is also the reason for contemporary war. The author presents the reasons for fighting among indigenous peoples in Chiapas and Yanomamas, who live on the border between Venezuela and Brazil. She finds out that at the one hand Indigenous peoples in Chiapas fight in a modern way, on the other hand Yanomamo peoples fight in a 'primitive' way.
Keywords: aggressiveness; agresivnost; bojevitost; vojne; primitivna ljudstva; staroselci; Mehika; Mexico; Chiapas; Yanomami